Ocular Toxoplasmosis Reactivation During Pregnancy – A Case Report - Olival, V (2011)
Introduction: Toxoplasmosis is caused by Toxoplasma gondii and may be acquired from food or water contaminated with cat feces or by vertical transmission. Severe fetal complications can overcome during pregnancy. There are also rare case-reports of congenital toxoplasmosis from previously immunized pregnant women; usually these women being had prior retinal toxoplasmic lesions. Immunosuppresion is one of the risk factors which accounts for some of these cases. Case report: 30 year-old pregnant woman, OI 2002, brazilian, previously healthy, admitted in Ophtalmology Department because of sudden left eye amaurosis in June, 2010. The fundoscopy revealed retinal scars suggesting previous infections; she was treated with corticoids and spiramycin for ocular toxoplasmosis reactivation. Previous serum analysis (2008) showed immunity to T. Gondii, but in July the IgM was negative and high levels of specific IgG were found (1227UI/mL). The serologic findings were later confirmed by a more accurate laboratory technique which found the IgM to be also positive. An amniocentesis was performed and it was negative for fetal transmission. Clinical and ultrasound follow-up throughout the rest of the gestational period was normal; daily spiramycin intake was maintained. An uneventful term delivery was performed. Neither the newborn’s serum analysis nor the histopathological study of the placenta were positive for congenital infection. Conclusion: Toxoplasmosis reactivation in pregnant women without immunosuppression is rare but is more likely to occur if previous post-infectious retinal scars are present. T. gondii infection is endemic in Brazil, so the geographical origin is important. If risk factors are present, fundoscopy should be performed every three months during pregnancy and one should always be aware of any visual symptoms. If you suspect reactivation, start medical prophylaxis for fetal transmission, perform amniocentesis and regular ultrasound follow-up.